Characteristics and weathering mechanisms of the traditional Chinese blue brick from the ancient city of Ping Yao. Issue 8 (19th August 2020) - Liu, Jian-bin; Zhang, Zhong-jian
Abstract : The traditional blue brick was the dominant clay brick used in Chinese architecture before the mid-nineteenth century. The ancient city of Ping Yao, a United Nations Educational, Scientific and Cultural Organization (UNESCO) heritage site, is an outstanding example of blue brick architecture. The Ping Yao bricks within the damp areas (up to 4 m at highest) of the ancient city's walls and private houses are subjected to various weathering, including contour scaling, flaking, powdering and salt crystallization. This study aims to characterize the properties, analyse weathering mechanisms, determine the main weathering factors and discuss the anti-weathering strategies of blue bricks. To do so, samples of brick and salt efflorescence were collected from the historical buildings of Ping Yao and were studied with regard to their mineralogical and physico-mechanical (e.g. density, porosity, pore size distribution, water absorption and uniaxial compressive strength) properties. The resistance to salt crystallization and frost, and the maximum firing temperatures of the brick samples were determined in the laboratory. Weathering mechanisms and anti-weathering strategies were discussed. Salt crystallization and freeze–thaw cycles were found to be two important factors that lead to brick weathering. An anti-weathering strategy of 'damp blocking, desalination and brick replacing' was discussed based on the laboratory experiments, suggestions in literature and site conditions.